Author Correction: Surface passivation of perovskite film for efficient solar cells - Jiang, Qi; Zhao, Yang; Zhang, Xingwang; Yang, Xiaolei; Chen, Yong; Chu, Zema; Ye, Qiufeng; Li, Xingxing; Yin, Zhigang; You, Jingbi (Nature photonics, 2019)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.